Game of thrones. The complete third season [videorecording (Blu-Ray)] - Benioff, David; Weiss, D. B. (Game of thrones (TV series), 2014)
In the third season of the HBO hit drama series Game of Thrones, the Lannisters barely hold on to the throne after a savage naval onslaught from Stannis Baratheon, while stirrings in the north threaten to alter the overall balance of power. Robb Stark, King in the North, faces major calamity in his efforts to build on his victories over the Lannisters while beyond the Wall, Mance Rayder and his huge army of wildlings continue their inexorable march south. Across the Narrow Sea, Daenerys Targaryen- reunited with her three fast-maturing dragons- attempts to raise an army to sail with her from Essos, in hopes of eventually claiming the Iron Throne. In Season 3 of this original series based on George R.R. Martin's bestselling books, the battling families of Westeros continue to clash as bonds are strained, loyalties are tested, and cruel fates are met.